2005
DOI: 10.1007/s00439-005-1260-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of adiponectin and obesity in Hispanic families: the IRAS Family Study

Abstract: Adiponectin, coded for by the APM1 gene, is a novel adipocyte-derived hormone implicated in energy homeostasis and obesity. Several genetic studies have observed evidence of association between APM1 gene polymorphisms and features of the metabolic syndrome, such as insulin resistance and obesity. As part of a comprehensive genetic analysis of the APM1 gene, we have screened 96 unrelated individuals for polymorphisms in the promoter, coding regions, and 3'untranslated region (UTR). Three promoter single-nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 37 publications
7
44
1
4
Order By: Relevance
“…In contrast, some other studies demonstrated that the common -11377C allele was strongly associated with obesity and MetS parameters (17,52). Our findings are also consistent with previous reports in different populations and different age groups (53,54,55) stating that ADIPOQ gene may play an important role in MetS. Results of these reports pointed that regional differences in body fat affected the risk of metabolic abnormalities, and also ADIPOQ gene variants were suggested as modulators of visceral fat accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, some other studies demonstrated that the common -11377C allele was strongly associated with obesity and MetS parameters (17,52). Our findings are also consistent with previous reports in different populations and different age groups (53,54,55) stating that ADIPOQ gene may play an important role in MetS. Results of these reports pointed that regional differences in body fat affected the risk of metabolic abnormalities, and also ADIPOQ gene variants were suggested as modulators of visceral fat accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…It is important to note that all three obesity traits have a high degree of correlation in the IRASFS (rX0.70; 31 ). Linkage results reported here are adjusted for age, gender, and center, but not BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The 30 SNPs examined encompassed the genomic region (25 kbp) containing ADIPOQ exons and introns plus 8 kbp upstream and 1 kbp downstream (chromosome 3: genome positions 188034376-188059821) and were selected from those listed in the National Center for Biotechnology Information database dbSNP build 129 or those described in published studies. Several of the SNPs have previously been associated with adiponectin level 32 and metabolic disorders including obesity, 33,34 type II diabetes mellitus, 24,28 or cardiovascular disease. 25 In addition, we only selected SNPs for which the minor allele frequency (MAF) was shown to be 41% in Japanese subjects.…”
Section: Selection Of Snpsmentioning
confidence: 99%